Tawhid and relevantisation of Qur'anic exegesis to Muslim political life: an exegetical interpretation of Al-Trabi's tafsir - Ibrahim, Esam Eltigani Mohamed; Zein, Ibrahim Mohamed (Revelation and Science, IIUM, 2014)
In his recently published Qur’ānic exegesis entitled al-Tafsīr al-Tawḥīdī, Hasan al-Turabi argued that the Qur’ānic discourse needs to be understood in accordance with the contemporary conditions of the Muslims. Its meanings must be interpreted in a rational and holistic manner. Most importantly, any attempt of a rationalistic interpretation must conform with the methodology of Tawḥīd. This research is an exegetical interpretation of al-Turabi’s writings about the concept of Tawḥīd and his thesis of Qur’anic exegesis. The research relies on analytic and inductive methodologies to reconstruct a coherent understanding of al-Turabi’s position on Qur’ānic exegesis. The main postulate of al-Turabi’s position is the utilization of Tawḥīd in a comprehensive way. This means that all of life including politics is a complete system geared toward worshiping Allah (ā). Based on this notion, al-Turabi criticized past and present Muslim scholars, asserting that they missed the essence of Tawḥīd when they divorce politics from religion after the era of the first guided khalifas. This situation left its impact on all the sciences of Islam including Qur’ānic exegesis. As a result, nowadays reciting and memorizing the Qur’ān does not serve the purpose of providing a guiding hand for public life. Because of this and other factors religiosity has become sheer hypocrisy or completely irrelevant. For this situation to be reformed and for Islam to be correctly implemented, the Qur’ān must be interpreted in such a way that makes it the sole guide for life without differentiating the private sphere from the public one. The importance of this research, therefore, is that it presents the contribution of one of the eminent figures in the international Islamic movement on the relevantisation of the Qur’ānic sciences to contemporary human life.